SURGICAL AND LASER TREATMENT CHIRURGICAL OF MAXILLARY OSTEITES - Bonchis Iuliu Alexandru (Romanian Society of Oral Rehabilitation, 2013)
Osteitis is an inflammatory process localized accurately at maxillary bones. From the surgical point of view of the procedure, the treatment should be very conservative. Laser therapy is a relatively new procedure in the dentistry field, but with remarkable results.